KAJIAN TERHADAP UU CIPTA KERJA KLUSTER LINGKUNGAN HIDUP ATAS DIHAPUSNYA PRINSIP STRICT LIABILITY - Nurul Listiyani; Rakhmat Nopliardy (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Indonesia adapted the concept of strict liability for the disposal of B3 (Hazardous and Toxic Materials) waste into the 1982 and 1997 Environmental Management Laws. However, only in the Environmental Management and Protection Act Number 32 of 2009 (UUPPLH), this principle more firmly listed. UUPPLH emphasizes that as long as there is an action that causes damage, the perpetrator must be responsible for restitution or compensation for damage to the victim without the need for supporting evidence. This principle has proven to be effective in instructing corporations to provide material compensation (ecosystem rehabilitation and compensation to victims) and immaterial (for example, counseling assistance to victims who have lost their livelihoods due to environmental damage). The enactment of Law Number 11 of 2020 concerning Job Creation/Omnibus Law as a national legal development policy directed at the ideological role model of legal centralism (legal centralism resulted in a shift in policy in the agrarian and environmental sectors. The abolition of the strict liability principle in the Job Creation Law will increase opportunities corporations escape legal proceedings for environmental crimes they commit and add to the burden on victims. From the normative study, it can be seen that the principle of absolute responsibility is used in carrying out a person's activity which is categorized as ultrahazardous (very dangerous) so that person has an obligation to bear all losses that arise. The disappearance of the phrase